2015
DOI: 10.1292/jvms.14-0071
|View full text |Cite
|
Sign up to set email alerts
|

A globotetraosylceramide (Gb<sub>4</sub>) receptor-based ELISA for quantitative detection of Shiga toxin 2e

Abstract: Currently, no simple assays are available for routine quantitative detection of Escherichia coli-produced Shiga toxin 2e (Stx2e) that causes porcine edema disease. Here, we present a novel quantitative detection method for Stx2e based on the measurement of Stx2e binding to the specific globotetraosylceramide (Gb4) receptor by ELISA (Gb4-ELISA). No cross-reactivity was found with the other Shiga toxins Stx1 and Stx2, indicating high specificity. When the recombinant Stx2e B subunit (Stx2eB) was used, the absorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
0
1
Order By: Relevance
“…Under this concentration, we were able to detect Stx2a as low as 23 ng/mL which met our need. In Gb4-based quantitative ELISA for Stx2e, the limit of detection is 20 ng/mL, 38 as comparable as ours. Moreover, two 96 well R-ELISA plates can be prepared from one vial of commercial available CTH (0.5 mg), instead of one 96 well plate if a higher concentration was used.…”
Section: Advances In Food Technology and Nutritional Sciences Issn 23supporting
confidence: 86%
See 1 more Smart Citation
“…Under this concentration, we were able to detect Stx2a as low as 23 ng/mL which met our need. In Gb4-based quantitative ELISA for Stx2e, the limit of detection is 20 ng/mL, 38 as comparable as ours. Moreover, two 96 well R-ELISA plates can be prepared from one vial of commercial available CTH (0.5 mg), instead of one 96 well plate if a higher concentration was used.…”
Section: Advances In Food Technology and Nutritional Sciences Issn 23supporting
confidence: 86%
“…First, we did not notice a correlation between Stx2 production and lineage. It was previously reported that E. coli O157:H7 isolates from lineage II produced less Stx2 than those from lineage I and I/II 28 ; however, our findings show that the Stx2 levels in strains from lineage II (PA40, 41) were not significantly different from strains belonging to lineage I (PA5, 31, 32, 49) or lineage I/II (PA22, 35,38,47). Second, although strains from clade 8 were suggested to produce higher Stx2 levels than isolates from other clades, 29,30 our data indicates this is not universal.…”
Section: Advances In Food Technology and Nutritional Sciences Issn 23contrasting
confidence: 80%